Quando o futuro é inscrito no passado: colonização e pioneirismo nas memórias públicas de Toledo-PR (1950-2010) - Langaro, Jiani Fernando (2012)
This work intent to establish some relationships between history and memory considering the ideas of colonization and pioneering disseminated in Toledo-PR, during 1950 to 2010. Trough this ideas were scattered many versions about a colonization private enterprise, achieved on Paraná West between 1940 and 1950, as a mark in history from local and regional past and as genesis of a fortunate journey which would raise a city in continuous progress . Such versions generally emphasizes just a few participations, like the ones connected to colonialist industries and clergy or southerner migrants which were European descendants, and keep in secret the negatives effects of that project, and this thought was accepted with no strings for some areas in local academic historiography. Initially, the hypothesis was that those memories grew from somewhere in the city, probably spread by some stiffs and social groups through institutions and projects, hypothesis that later on was proved. Having this as beginning point, and basing on social history knowledge, the target turn into the study of how these memories were established and became hegemonics in that place, the different elements emerged from wrangles and any other ways to explain the local past. In this way, drawing heavily on sources like recolection literature, printing press, schoolbooks, monuments and spaces on the city or on entities that studied local past, many cultural and educational projects created by the public authorities and independent initiatives turned questionable. From this point, it is possible to certify that in Toledo existed a battlefield for the past in which city foundation memories acquired centrality and became groundwork to picture the future. More than this, such wrangles involved local academic historiography its own and make clear that history and memories were attached to social reality. Through oral narratives it was also observed that in the admission of these memories the inhabitants did not just absorb than, but reflected and elaborated it again, this is what makes possible to perceive the existence of hegemonic versions, but not unique, about Toledo and Paraná West past